2015
DOI: 10.1111/cen.12751
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of vitamin D in pregnancy and its correlation with feto‐maternal outcome

Abstract: Vitamin D supplementation reduces risk of maternal comorbidities and helps improve neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
192
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(206 citation statements)
references
References 38 publications
3
192
0
2
Order By: Relevance
“…40 Furthermore, studies with sample size >100, low risk of bias, and single-dose vitamin D supplementation all showed that vitamin D supplement could reduce the risk of PTB, but we could not draw a conclusion because the subgroups had only one or two RCTs, and the results may be misleading. Sensitivity analysis of RCT indicated that the Sablok et al 34 and Grant et al studies 37 could both significantly affect the results. A possible reason is that the small sample size generated less stable results, therefore it is difficult to exclude the possibility that the positive association is due to chance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 Furthermore, studies with sample size >100, low risk of bias, and single-dose vitamin D supplementation all showed that vitamin D supplement could reduce the risk of PTB, but we could not draw a conclusion because the subgroups had only one or two RCTs, and the results may be misleading. Sensitivity analysis of RCT indicated that the Sablok et al 34 and Grant et al studies 37 could both significantly affect the results. A possible reason is that the small sample size generated less stable results, therefore it is difficult to exclude the possibility that the positive association is due to chance.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 lists the characteristics of the 18 observational studies 9,[12][13][14][15][16][17][18][19][20][21][22][23][24][30][31][32] and six RCT. [33][34][35][36][37][38] There was some disparity in the definition of PTB between studies. Most studies defined PTB as delivery before 37 weeks' gestation, but two studies used a threshold of <35 weeks.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies [19, 20, 21, 22] were randomized controlled trials (RCTs).Two studies [23, 24] were post hoc analyses of RCT. Prospective cohort design was applied by six studies [25, 26, 2729, 30].…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological data have shown that deficiency during pregnancy causes higher risk of maternal preeclampsia [55][56][57][58], gingivitis, and periodontal disease in the mother [59,60] and impaired fetal growth [61,62], impaired dentition [63,64], and increased risk of respiratory syncytial virus infection [65] in the infant. A recent RCT in India showed that women who were given vitamin D supplementation during pregnancy had a 61% lower risk of preterm labor and a 47% lower risk of hypertensive complications compared to participants who were not given supplementation [66]. In another RCT, vitamin D supplementation of 4000 IU/day was shown to be safe and effective in achieving sufficiency (32 ng/mL) for pregnant women and their infants, whereas 400 IU/day was ineffective [67][68][69].…”
Section: Pregnancymentioning
confidence: 99%